Двадцать тысяч лье под водой - Верн Жюль (Всемирная классика приключений, 2014)
Экземпляры: 22 (20210712) / Инвентарный номер: 66486 / Цена: 200.00 / Сис.шифр: 84(4Фра) / Авт.знак: В 35 / ГРНТИ: 17.82.31 / ББК: 84(4Фра)